OPC UA Stack och SDK i Delphi riktat mot färdigt miljöredovisningssystem - BJÖRKLUND, WILLIAM; DAHLBERG, VICTOR (My University, 2017)
This project concerns the necessity of the OPC UA standard for communication as well as the implementation of a OPC UA communication stack and client in the Delphi programming language. OPC UA is the newer standard for communication developed by the OPC Foundation to ensure greater future flexibility and compatibility with different operating systems and security algorithms. The client application may discover and communicate with different servers locally or via the internet by means of messages utilising the standard’s predefined message structures for opc.tcp. Loss of connectivity and power by the client is handled and options for prepared configurations are in place to ensure the viability of quick subscription to data values on the desired server.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science